Molybdenum isotope fractionation during adsorption to organic matter. (1st February 2018) - King, E.K.; Perakis, S.S.; Pett-Ridge, J.C.
Abstract: Organic matter is of emerging interest as a control on molybdenum (Mo) biogeochemistry, and information on isotope fractionation during adsorption to organic matter can improve interpretations of Mo isotope variations in natural settings. Molybdenum isotope fractionation was investigated during adsorption onto insolubilized humic acid (IHA), a surrogate for organic matter, as a function of time (2–170 h) and pH (2–7). For the time series experiment performed at pH 4.2, the average Mo isotope fractionation between the solution and the IHA (Δ 98 Mosolution-IHA ) was 1.39‰ (±0.16‰, 2σ, based on 98 Mo/ 95 Mo relative to the NIST 3134 standard) at steady state. For the pH series experiment, Mo adsorption decreased as pH increased from 2.0 to 6.9, and the Δ 98 Mosolution-IHA increased from 0.82‰ to 1.79‰. We also evaluated natural Mo isotope patterns in precipitation, foliage, organic horizon, surface mineral soil, and bedrock from 12 forested sites in the Oregon Coast Range. The average Mo isotope offset observed between precipitation and organic (O) horizon soil was 2.1‰, with light Mo isotopes adsorbing preferentially to organic matter. Fractionation during adsorption to organic matter is similar in magnitude and direction to prior observations of Mo fractionation during adsorption to Fe- and Mn- (oxyhydr)oxides. Our finding that organic matter influences Mo isotope composition has important implications for the role of organic matter as a driver of trace metal retention and isotopic fractionation.